2022
DOI: 10.1371/journal.pone.0279761
|View full text |Cite
|
Sign up to set email alerts
|

Three-minute bench step exercise as a countermeasure for acute mental stress-induced arterial stiffening

Abstract: Acute mental stress (MS) induces a transient increase in arterial stiffness. We verified whether a single bout of bench step (BS) exercise for 3 minutes counteracts acute MS-induced arterial stiffening. Fifteen healthy young men (mean age, 21.7 ± 0.3 years) underwent two experimental trials: rest (RE) and exercise (EX) trials. Following a 5-minute MS task, the participants in the RE trial rested on a chair for 3 minutes (from 10 to 13 minutes after task cessation), whereas those in the EX trial performed the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Thus, engagement in feasible short-duration exercise every time a stressful situation arises may be more beneficial than coping with multiple stress exposures using a single exercise bout. As such, in our most recent study 39) , we have revealed that BS exercise for only 3 min is sufficiently effective in reversing an arterial stiffness increase induced by acute MS (Fig. 3).…”
Section: Exercise As Countermeasure For Detrimental Vascular Impacts ...supporting
confidence: 50%
See 1 more Smart Citation
“…Thus, engagement in feasible short-duration exercise every time a stressful situation arises may be more beneficial than coping with multiple stress exposures using a single exercise bout. As such, in our most recent study 39) , we have revealed that BS exercise for only 3 min is sufficiently effective in reversing an arterial stiffness increase induced by acute MS (Fig. 3).…”
Section: Exercise As Countermeasure For Detrimental Vascular Impacts ...supporting
confidence: 50%
“…In our studies, the 10-min cycling or BS exercise were performed at 35.4% and 38.8% of the heart rate reserve (HRR), respectively 37,38) , which is classified as light-intensity aerobic exercise 44) . On the other hand, in the 3-min BS exercise study, participants exercised to meet a rate of perceived exertion of 11-13 (Borg scale, 6-20), and consequently achieved 49.1% of the HRR 39) ; this corresponds to the moderate-intensity domain 44) . The minimum exercise intensity and duration required to counteract the detrimental vascular impacts of acute MS is currently unknown.…”
Section: Exercise As Countermeasure For Detrimental Vascular Impacts ...mentioning
confidence: 99%